2020
DOI: 10.1021/acs.macromol.0c01444
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ion Transport in Lithium Salt-Doped Polymeric Ionic Liquid Electrolytes

Abstract: Recent experimental results have demonstrated that polymeric ionic liquids doped with Li salts exhibit enhanced ionic mobilities and lithium ion transference numbers with increasing salt concentrations. In this study, we used atomistic molecular dynamics simulations on a model system of lithium salt-doped 1-butyl-3-methyl-imidazolium bistriflimide ionic liquids and poly­(1-butyl-3-methyl-imidazolium bistriflimide) electrolytes to identify the molecular mechanisms underlying such findings. Our results mirror qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(80 citation statements)
references
References 78 publications
4
67
1
Order By: Relevance
“…The molecular structure of the studied PIL with cationic polymer backbone excludes these oxygen-related ion-hopping mechanisms. Instead, TFSI related transport mechanisms of the lithium-ions are proposed in the literature [ 23 ]. Even through, it is not possible to distinguish between the anions and cations influence on the ionic conductivity in the performed EIS measurements, comparable PEO membranes appear to have superior overall ionic conductivities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The molecular structure of the studied PIL with cationic polymer backbone excludes these oxygen-related ion-hopping mechanisms. Instead, TFSI related transport mechanisms of the lithium-ions are proposed in the literature [ 23 ]. Even through, it is not possible to distinguish between the anions and cations influence on the ionic conductivity in the performed EIS measurements, comparable PEO membranes appear to have superior overall ionic conductivities.…”
Section: Resultsmentioning
confidence: 99%
“…According to Zhang et al the movement of lithium-ions through a TFSI-PIL system is coupled to a coordination of the lithium cations to the TFSI anions in different simultaneously occurring transport mechanisms [ 23 ]. The lithium-ions can either move as a kind of naked cations from one TFSI-coordination shell to another (structural movement) or within a fixed TFSI-complex shell from one cationic PIL center to another (vehicular movement) [ 23 ]. With increasing lithium concentration the overall lithium mobility increases and the vehicular movement is getting more influence over the structural movement [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ganesan and coworkers demonstrated in their atomistic molecular dynamics simulations that the vehicular mode is dominant in LiFSI‐doped poly(1‐butyl‐3‐methyl‐imidazolium bistriflimide) electrolytes. [ 57 ] They also suggested that polymer segmental dynamics is quite important in Li + mobility since the Li + is indirectly connected to the polymer chains through Li‐anion‐polycation bridges, indicating that the co‐coordination mode’ importance. Besides, Sokolov and coworkers provided with useful insights regarding ionic correlations in polyIL electrolytes.…”
Section: Well‐defined Polymer Matricesmentioning
confidence: 99%